GENETIC INFORMATION AND PERSONAL DATA UNDER CONDITIONS OF DIGITAL TRANSFORMATION - Rassolov, Ilya M.; Chubukova, Svetlana G.; Mokhov, Alexandr A.; Shagieva, Rosalina V. (International Journal of Psychosocial Rehabilitation, 2020)
Breakthrough discoveries in genetic research, gene therapy and genetic engineering have brought significant advances for humanity. The results of scientific research and the open possibilities of editing the human genome provide geneticists with an instrument that can rid humanity of terrible diseases and may even lead to the emergence of new racial theories and the violation of universally recognized human rights and freedoms. The purpose of the article is to develop scientifically grounded and verified legislative practice of Russia and the European Union of terminology: "genetic information" and "personal data" to test proposals for the development of Russian legislation on genetic information in the digital transformation. The leading methods of studying this problem are the formal legal method and the method of comparative jurisprudence. These methods have allowed to consider the problem put in article as process of purposeful and conscious mastering by geneticists, physicians and biologists of legal knowledge, skills and abilities to carry out information and legal actions in digital sphere at processing of the genetic information based on requirements of the international and national legislation. The article presents the author’s solution of legal problems arising in the process of automated processing and exchange of genetic information by medical, research and state organizations. Originality/value: The developed theoretical provisions and proposals to improve the legislation on genetic information are aimed at training lawyers, physicians and biologists who use modern information technologies to process genetic information.